PERAN GURU DALAM MENGEMBANGKAN KETRAMPILAN COLLABORATION PESERTA DIDIK MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA MATA PELAJARAN MATEMATIKA KELAS l MI TARBIYATUL ATHFAL PATI TAHUN AJAR 2026/2027 - Abdul Manaf, Zulfan; Faila Sufa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of teachers in developing students’ collaboration skills through the Pancasila Student Profile Strengthening Project (P5) in first-grade mathematics instruction at MI Tarbiyatul Athfal Pati during the 2026/2027 academic year. This study aims to examine how teachers facilitate collaboration skills and to identify the factors that support and hinder their implementation. This study employs a qualitative descriptive approach with a field research design. Data sources include primary data from the school principal, teachers, and students, as well as secondary data from relevant documents. Data collection techniques involved observation, interviews, and documentation, while data analysis utilized data reduction, data presentation, and drawing conclusions. The research results indicate that the role of teachers in developing collaboration skills through P5 activities is carried out in three stages: planning, implementation, and evaluation. During the planning stage, teachers develop instructional modules based on the Madrasah Operational Curriculum and design project activities that encourage student interaction and cooperation. During the evaluation phase, teachers assess the process and outcomes of group work, including participation, communication, and collaboration skills. Supporting factors include teacher professionalism and creativity, the role of the school principal in learning evaluation, and student enthusiasm and active participation. Hindering factors include limited facilities and infrastructure, as well as low student self-confidence.